Development of predictive models for power performance based on anthropometric variables in amateur football players - Nik Zahib, Nik Suzairan; Abd Rahman, Harith Rusydin; Zaker, Nur Amirah; Jamaludin, Masshera; Abu Bakar, Al Hafiz; Ismail, Ahmad Dzulkarnain; Ismail, Zulkifli (Universiti Teknologi MARA, Perlis, 2025)
This study aims to determine the correlation between selected anthropometric variables and power ability, and to develop predictive models for power ability. Fifteen male players from UiTM Perlis FC (aged 20.87 ± 1.19 years) were recruited for this study. The anthropometric variables were measured using different instruments, including body weight, height, body mass index, body fat percentage, waist circumference, hip circumference, calf circumference, thigh circumference, ankle circumference, leg length, foot length and fat-free mass. Power ability was assessed using the countermovement jump (CMJ) test. Pearson correlation was used to analyze relationships between anthropometric variables and power, while multiple regression was applied to develop predictive models for power. The results showed that there was a significant relationship between power ability and body weight (r = 0.79), fat-free mass (r = 0.83), body mass index (r = 0.64), waist circumference (r = 0.66), hip circumference (r = 0.69), calf circumference (r = 0.58), thigh circumference (r = 0.67), and ankle circumference (r = 0.61), p ≤ 0.05. The predictive model for power ability is = 315.819 - (18.572) body weight + (57.922) fat-free mass + (83.478) body mass index - (1.095) waist circumference - (36.472) hip circumference + (4.107) thigh circumference. In conclusion, anthropometric variables significantly correlate with amateur football players' power ability. Therefore, coaches and practitioners should emphasize developing these variables to enhance power performance.